1985
DOI: 10.1038/icb.1985.24
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization Kinetic Analysis of Echovirus 30 and Coxsackievirus B4 Strains Revealed Little Antigenic Variation Amongst the Echovirus Strains

Abstract: Summary. An antigenic analysis was made of echovirus 30 and coxsackievirus B4 isolates by determining neutralization rate constants in neutralization kinetic tests. The seven echovirus 30 isolates included the prototype strain and six others isolated in Melbourne, Australia, between 1959 and 1982. Little antigenic heterogeneity was observed in contrast to the evidence of antigenic variation recorded in similar tests on seven coxsackievirus B4 isolates. These isolates also included the prototype strain, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…However, few studies have been made of this variation in echovirus serotypes, and contrasting results have been obtained. Echovirus types 7, 11, and 17 were found to vary antigenically by neutralization kinetic analysis (15), whereas antigenic constancy was found among echovirus type 30 isolates (1).…”
mentioning
confidence: 99%
“…However, few studies have been made of this variation in echovirus serotypes, and contrasting results have been obtained. Echovirus types 7, 11, and 17 were found to vary antigenically by neutralization kinetic analysis (15), whereas antigenic constancy was found among echovirus type 30 isolates (1).…”
mentioning
confidence: 99%
“…Such intratypic variation has been described previously in group B coxsackieviruses; community enteroviral isolates collected longitudinally from the same geographic area have been found to diverge antigenically from the prototype viruses [Ash et al, 1985;Richter et al, 19721. Our data indicate that significant intratypic variation also occurs in a region of the genome that does not encode viral proteins.…”
Section: Enteroviralmentioning
confidence: 80%
“…Enteroviral isolates from the second CSF of both patients were identified by serotyping as CB3, while viral cDNA sequences derived from those CSF samples were different from the CB3 prototype virus as well as from each other. Such intratypic variation has been described previously in group B coxsackieviruses; community enteroviral isolates collected longitudinally from the same geographic area have been found to diverge antigenically from the prototype viruses [Ash et al, 1985;Richter et al, 19721. Our data indicate that significant intratypic variation also occurs in a region of the genome that does not encode viral proteins. Unfortunately, CSF viral cultures were not done during the first illness of either of the patients in this study.…”
mentioning
confidence: 99%
“…Recently it was shown that new isolated E25 strains have become increasingly difficult to identify by the neutralizatioil test because of antigenic variations [Peigue-Lafeuille et al, 1990, 19921. E7, E l l , E l 7 also vary antigenetically by neutralization kinetic analysis, whereas more antigenic constancy was found for E30 [Ash et al, 1985;Kirkwood et al, 19881. Our findings support the suggestion that the great majority of enteroviruses may be divided roughly into two larger subgroups, first consisting of polioviruses and certain coxsackie A viruses and the second including coxsackie B viruses, most echoviruses and representatives of coxsackie A viruses [Zhang et al, 1993;Zoll, 19941. More sequence data are still needed for the exact classification of enteroviruses.…”
Section: Discussionmentioning
confidence: 99%